1990
DOI: 10.1104/pp.94.2.531
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbate Free-Radical Reduction by Glyoxysomal Membranes

Abstract: Glyoxysomal membranes from germinating castor bean (Ricinus communis L. cv Hale) endosperm contain an NADH dehydrogenase. This enzyme can utilize extraorganellar ascorbate freeradical as a substrate and can oxidize NADH at a rate which can support intraglyoxysomal demand for NAD@. NADH:ascorbate free-radical reductase was found to be membrane-associated, and the activity remained in the membrane fraction after lysis of glyoxysomes by osmotic shock, followed by pelleting of the membranes. In whole glyoxysomes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
32
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 29 publications
2
32
0
Order By: Relevance
“…In glyoxysomal membranes, MDHAR appears to have a tuans-membrane orientation similar to that found on the outer mitochondria membranes in chromaffin vesicles (Bowditch and Donaldson, 1990;Njus and Kelley, 1993). Latency experiments of intact pea mitochondria and peroxisomes showed a high latency of MDHAR activity (about 90%) in both organelles, suggesting that the electron acceptor and donor sites of MDHAR activity are not in a cis orientation in the external side of the outer mitochondrial membrane and the cytosolic side of the peroxisomal membrane.…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…In glyoxysomal membranes, MDHAR appears to have a tuans-membrane orientation similar to that found on the outer mitochondria membranes in chromaffin vesicles (Bowditch and Donaldson, 1990;Njus and Kelley, 1993). Latency experiments of intact pea mitochondria and peroxisomes showed a high latency of MDHAR activity (about 90%) in both organelles, suggesting that the electron acceptor and donor sites of MDHAR activity are not in a cis orientation in the external side of the outer mitochondrial membrane and the cytosolic side of the peroxisomal membrane.…”
Section: Discussionmentioning
confidence: 86%
“…The inhibition of mitochondrial and peroxisomal APX by aminotriazole has also been observed in other APX isozymes (Foyer et al, 1994). In glyoxysomal membranes from castor bean endosperm, Bowditch and Donaldson (1990) demonstrated the presence of membrane-associated MDHAR activity and found that this activity was due to the 32-kD glyoxysomal membrane protein responsible for the ferricyanide reductase activity previously characterized in those membranes (Luster et al, 1988). Recently, the integral membrane polypeptides of pea leaf peroxisomes were characterized (López-Huertas et al, 1995), and the 32-kD membrane polypeptide was identified as a flavoprotein with NADH: ferricyanide reductase activity, which is also able to generate NADH-dependent 0;-radicals (LÓpez-Huertas et al, 199613).…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations